ELECTROMECHANICAL PRESSURE SENSORS BASED ON GRAPHENE: A REVIEW - Al-mashaal, Asaad K. Edaan (International Journal Multidisciplinary (IJMI), 2024)
Objective: This review explores the potential of graphene, a two-dimensional carbon allotrope, in revolutionizing pressure sensors. Graphene's exceptional electrical and mechanical properties enable significant advancements in sensitivity, dynamic range, response time, and flexibility, addressing limitations in traditional sensor technologies. Methods: The study examines the fundamental mechanisms of graphene-based pressure sensors, including piezoresistive, capacitive, and field-effect transistor (FET) mechanisms. A comparative analysis of conventional materials such as piezoelectric, metallic, silicon, and polymer-based materials is conducted to highlight their strengths and limitations. The integration of nanomaterials, particularly graphene, into sensor designs is reviewed, emphasizing their contributions to enhanced sensor performance. Results: Graphene-based sensors demonstrate superior sensitivity and miniaturization capabilities due to their high surface-to-volume ratio, tunable electrical conductivities, and mechanical resilience. Emerging applications in healthcare, electronics, and robotics validate the transformative impact of graphene on sensor technologies. Novelty: This review underscores the unique advantages of graphene over traditional materials, emphasizing its potential to address challenges related to sensitivity, response time, and durability in extreme conditions. Future research directions are proposed to overcome existing limitations and expand the scope of graphene-based sensors across diverse industries.